Effectiveness of the TARL approach assisted by ZEP QUIZ on students’ conceptual understanding of three-variable linear equation systems - Revita Lestari; Rizky Esti Utami; Dhian Endahwuri (UNION : Jurnal Ilmiah Pendidikan Matematika, 2026)
This study aims to analyze the effectiveness of the Teaching at the Right Level (TARL) approach supported by ZEP QUIZ on students' mathematical concept comprehension abilities in Three Variable Linear Equation Systems (TVLES) material at SMA Negeri 1 Subah. However, studies integrating TARL with digital tools such as ZEP QUIZ in high school algebra remain limited. This study uses a quantitative approach with a posttest-only control group quasi-experimental design. The sample consisted of two classes selected purposively, namely the experimental class that received TARL learning with the help of ZEP QUIZ and the control class that received conventional learning. The research instruments were concept comprehension tests and student activity observation sheets. The data were analyzed using normality and homogeneity tests, Independent Sample t-Test, classical mastery analysis, and simple linear regression. The results showed that the average posttest score of the experimental group significantly outperformed the control group and achieved high classical mastery. Student activity also showed a strong positive effect on conceptual understanding. Thus, the ZEP QUIZ-assisted TARL approach was effective in improving students' mathematical conceptual understanding of TVLES material. This study contributes by providing empirical evidence on the integration of level-based adaptive learning and interactive digital tools to enhance students’ conceptual understanding in high school algebra.